Evaluasi Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja pada Pekerjaan Gedung Apartemen Begawan Malang - Pakereng, Rizal ; Suhudi ; Wijaya , Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The implementation of occupational safety and health management systems in construction projects has now become a major concern for construction service developers. To measure the success of the implementation of a work safety and health management system for a construction project, the author conducted research on the work of the Begawan Apartment Building in Malang. The method used in this research is a quantitative method for measurement based on existing theories and univariate analysis method for analysis of one variable. From the results of the study it can be concluded that the success rate of the implementation of occupational safety and health management systems in the work of Begawan Apartment Building Malang reached a value of 89.80%. In accordance with Labor Minister Regulation No. 05 of 1996 that achieving the application of the value of 85-100% deserves to be given a gold flag certificate and award.